PENGARUH POLUTAN TAMBAK TERHADAP EFISIENSI TEKNIS PRODUKSI BANDENG DI KABUPATEN KARAWANG - Lilis Imamah Ichdayati; Sri Hartoyo; Yusman Syaukat; Sri Utami Kuntjoro (Jurnal Agribisnis Indonesia, 2013)
This study uses two models of stochastic frontier production function Cobb Douglas separate to estimate differences in environmental efficiency of conventional input variables and input variables detrimental. The results that farms with milkfish monoculture and polyculture cultivation pattern majority (approximately 82 percent) have reached a technically efficient, with an average efficiency rate of 0826.  Effect of pollutants on the efficiency of production of milkfish ponds visible from reduced levels of technical efficiency of the 0826 in model 1 becomes 0.633 in model 2 , so that the influence of pollutants by 0193. The decrease in efficiency is derived from the nitrogen pollutants are negative and significant. Policy implications necessary to supervise the use of the excessive feed and urea.